Concept-Based Instruction as an Innovation to Improve Grade 5 Learner’s Metaphoric Competence - Samosa, Prof. Resty C.; Admana, Clarry Jane; Almia, Vincent; Garcia, Verlan Jane; Lorilla, Marvin Roi (European Journal of Life Safety and Stability (2660-9630), 2021)
This study uses Concept-Based Instruction in teaching metaphors to the ESL learners. Concept-based curriculum and instruction is a critical link in making learning more relevant and interesting for students. This study aims to shed light to the teaching and learning of metaphors using Concept-Based Instruction in the context of English as a Second Language learners. It aims to explore how the concept‐based approach influences their development of metaphorical competence. The major concern of this study is to determine the effectiveness of Concept-based instruction approach in improving Grade 5 ESL learners' metaphorical competence in assessing the improvement of the subjects. The study assessed the Concept-Based Instruction as an Innovation to improve Grade 5 learner’s metaphoric competence in the selected private school students in the Schools Division of San Jose del Monte, Bulacan. The Respondents of the study were purposively selected which compromised of Twenty-eight (28) from the private school students in the Schools Division of San Jose del Monte, Bulacan. The goal of CBI is to stimulate development through the effective presentation of high-quality conceptual knowledge linked to practical activity, in which students not only internalize the conceptual knowledge but also learn how to apply it to their own goals in any of the school subjects taught, including language. The study revealed there is a significant difference in the pretest and posttest score of the students in the utilization of the Innovation in improving the learners’ metaphoric competence.